PhET simulation in education: A bibliometric analysis of the Scopus database - Fatma Suryani Harahap; Eko Susetyarini; Elly Purwanti; Sulidar Fitri; Nia Kurniaty Rukman; Heni Mulyani Pohan (Universitas Muhammadiyah Malang, 2025)
The advancement of digital technology has significantly transformed approaches to science and mathematics education, notably through the use of interactive simulations. One of the most prominent innovations is PhET Simulations, widely employed to enhance conceptual learning and 21st-century skills. This study aims to analyze the trends and contributions of PhET Interactive Simulations in science and mathematics education through a bibliometric approach based on Scopus data (2006–2024). Using the PRISMA method, 82 selected articles were analyzed via VOSviewer and CSV to map publication dynamics, citations, international collaborations, and research focus. The results indicate a significant increase in publications since 2017, peaking in 2020–2021 due to technology adoption during the COVID 19 pandemic. Indonesia dominates in publication quantity (40 documents), while the United States leads in citation influence. Key topics include enhancing conceptual understanding, integrating problem-based learning (PBL) models, and utilizing interactive simulations for critical thinking skills. Early publications (2006–2008, remain the most influential references with 263 citations. However, the study identifies gaps, including limited research on long-term impacts, cultural context variations, and educators’ roles in simulation-based learning. This analysis recommends exploring PhET integration in STEM models, developing adaptive pedagogical strategies, and conducting comparative studies on simulation vs. conventional methods. The findings underscore PhET’s critical role as a transformative tool in digital education, particularly in facilitating exploratory and collaborative learning.